Chip‐Based Heat Stimulation for Modulating Signal Propagation in HL‐1 Cell Networks. Issue 12 (24th September 2018) - Dang, Ka My; Rinklin, Philipp; Afanasenkau, Dzmitry; Westmeyer, Gil; Schürholz, Tobias; Wiegand, Simone; Wolfrum, Bernhard
Abstract: Signal propagation in cardiac cell networks can be modulated by heat stimulation. Here, the response of a connected HL‐1 cardiomyocyte cell network to the application of confined heat stimuli using Ca 2+ imaging is investigated. Localized temperature gradients are generated by resistive heating via microwire arrays on a chip surface, which serves as a substrate for growing a confluent cell network. It is demonstrated that upon heat stimulation, the velocity of the propagating Ca 2+ wave in the network is locally increased, leading to a deformation of the wavefront. Furthermore, evidence of a change in the signal propagation direction caused by a relocation of the pacemaker cell is shown. This effect might be used in future applications, where heat is employed as an alternative modality for cell stimulation protocols. Abstract : It is demonstrated that local heat stimulation can increase the velocity of Ca 2+ waves in cardiomyocyte‐like cell networks leading to a deformation of the wavefront. Furthermore, evidence of heat‐induced changes in the signal propagation direction possibly caused by a relocation of the pacemaker cell is shown.